VIDEO BLOGGING: A PEDAGOGICAL MEDIA TO IMPROVE SPEAKING SKILL - Nufus, Tatu Zakiyatun (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2023)
Technology is considered as a learning assistant that can be used to improve speaking skills. In this paper, the researcher tried to enhance students’ speaking skills using English video blogging. The purposes of this research were to know how students’ perception of the use of English video blogging in speaking skills and to what extent video blogging improves students’ speaking skills. This study was done in one High school at Tangerang- Banten with 25 students in Grade XI. This study is a qualitative design with descriptive analysis in interpreting data, in data collection, the researcher used an observation (participatory observation) and depth interview with the participants. The result shows that students’ perceptions of the use of English video blogging to improve speaking skills are good and successful, and it can be seen about 80 % of the participant are having a good improvement in speaking ability. And the rest of them still feel lack confidence and fluency in speaking. Finally, the use of video blogging in classroom activities gives a good impact on students’ speaking skills.